PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN DAN KEPRIBADIAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN PADA MAHASISWA DI KOTA JAMBI - Jaker, Mohd; Majid, Nazori; Mutia, Agustina (Manajemen Keuangan Syariah, 2023)
The era of the industrial revolution 5.0 inIndonesia is currently making society as modern humans must have financial intelligence, namely intelligence in managing being responsible for their personal finances so as not to cause an imbalance between income and expenses which will also have an impact on the level of welfare of the individual's life.This research is a quantitative research with primary data as the data source used. The population in this study were 7 Islamic tertiary institutions in Jambi City with a total of 14,760 students. There are three data analyzes used in this study, namely the classic assumption test which consists of a normality test, multicollinearity test and heteroscedasticity test. The results showed that the classical assumption test had been fulfilled. Based on the results of testing the financial literacy variable (X1) it influences financial management behavior with a significance level of 0.013. The financial attitude variable (X2) has an effect on financial management with a significance level of 0.000. Spiritual intelligence variable (X3) has no effect on financial management with a significance level of 0.268. Meanwhile, the financial literacy variables, financial attitudes and financial intelligence jointly affect student financial management. Keywords: Financial Literacy, Spiritual Intelligence, Financial Management Â